Peran Arsiparis dalam Menjamin Keaslian Dokumen Pejabat Publik - Setiawan, Laksamana Aryaputera; Nailatusysyarofah, Falihah; Nurazkya, Elgalia Salsabila; Al Ghifari, Hanif Rasha; Claudia, Iela; Agusta, Devianindya; Savero, Devara Favian (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2025)
The authenticity of public officials documents is an important foundation for the legitimacy, accountability, and public trust in government institutions. Archivists have a strategic responsibility to ensure the authenticity and integrity of documents that serve as legal evidence of public officials’ administrative actions. This study aims to analyze the role and function of archivists in ensuring the authenticity of public officials’documents, particularly through the processes of verification,authentication,and preservation of archives. The research method uses a qualitative approach with a literature study of national archival regulations,international standards,and best practices in archive management in government agencies. The results of study show that archivists play a role in four main aspect: (1) verification of the structure and physical integrity of documents; (2) maintenance of the chain of custody of documents; (3) application of authenticity standards in accordance with the National Archives Regulation; and (4) digitization and long-term preservation to ensure the accessibility of authentic documents. The competence of an archivist in document forensics,metadata management, and archival information systems is key to preventing forgery and supporting the provision of valid evidence. The implications of the study emphasize the need to increase the capacity of archivists through continuous training, strengthening the regulatory framework, and integrating digital technology into the authentication process to strengthen public trust in the integrity of public officials documents in the digital age.